The clinical and histopathological characteristics of early‐onset basal cell carcinoma in Asians. (29th June 2016) - Yang, M.Y.; Kim, J.M.; Kim, G.W.; Mun, J.H.; Song, M.; Ko, H.C.; Kim, B.S.; Kim, H.S.; Kim, M.B.
Abstract: Background: Basal cell carcinoma (BCC) is by far the most common cancer in white populations. In addition, recent reports have demonstrated an increasing incidence of BCC in Korea. We have observed a significant number of early‐onset BCC cases in which the disease occurred in patients younger than 50 years. Objective: To investigate the clinicopathological characteristics of early‐onset BCC in an Asian population, specifically in Koreans. Methods: One hundred and five patients with early‐onset BCC were enrolled from a total of 1047 BCC patients who underwent surgery between January 1997 and December 2014 (942 patients over the age of 50 years were designated as the control group). Results: Early‐onset BCC accounted for 10.03% of all 1047 cases and the incidence over time displayed an incremental trend. The early‐onset group displayed similar results as the control group, with a predominance of female BCC patients and the majority of tumours displaying the following characteristics: small in size, occurring in sun‐exposed areas and belonging to the noduloulcerative clinical subtype and nodular histopathological subtype. In comparison with a previous study in a Western population, the incidence of the disease in non‐exposed areas of the body, as well as the proportion of tumours of the superficial histological subtype, were lower in Asian patients. Conclusion: Although the clinicopathological characteristics of BCC are well‐known, these characteristics have not been determined for early‐onset BCC in an Asian population. Therefore, this study is the first report on early‐onset BCC in Asians, specifically in a Korean patient group.